Serum MMP7, MMP10 and MMP12 level as negative prognostic markers in colon cancer patients. Issue 1 (December 2016) - Klupp, Fee; Neumann, Lena; Kahlert, Christoph; Diers, Johannes; Halama, Niels; Franz, Clemens; Schmidt, Thomas; Koch, Moritz; Weitz, Juergen; Schneider, Martin; Ulrich, Alexis
Abstract Background Matrixmetalloproteinases (MMPs) comprise a family of zinc-dependent endopeptidases which are involved in angiogenesis, tumor invasion and metastatic formation. Up to date, the prognostic relevance of MMPs in serum of patients with colon cancer remains unknown. Thus, we wanted to assess an expression pattern of MMPs in a homogenous cohort of colon cancer patients to assess their potential as prognostic biomarkers. Methods Differences in the expression pattern of MMP7, MMP10 and MMP12 in 78 serum specimens of patients with an adenocarcinoma of the colon and serum specimens of a healthy control group were assessed using Luminex-100 technologies. Subsequently, we correlated these results with histopathological and clinical data of the patients. Results Luminex based expression analysis revealed a significant overexpression of MMP7 and an overexpression of MMP10 and MMP12 in the sera of colon cancer patients compared to the healthy control group. Patients with vascular invasion showed a significantly higher MMP12 expression than V0-staged patients. Moreover overexpression of MMP7, MMP10 and MMP12 in colon cancer patients´ sera displayed a significantly impaired overall survival. Multivariate analysis revealed high MMP10 serum levels to be an independent adverse prognostic marker in colon cancer patients. Conclusions Expression patterns of MMP7, MMP10 and MMP12 in colon cancer patients´ sera are different compared to serum specimens of healthy individuals. Furthermore, overexpression of MMP7, MMP10 and MMP12 in colon cancer patients´ sera correlates with a dismal prognosis and may help to stratify patients into different risk groups.